2010
DOI: 10.1111/j.1365-2893.2010.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and prevention of hepatitis B virus infection in China

Abstract: SUMMARY. The concept of a hepatitis B vaccine was first introduced into China in 1978. China has been one of the first two developing countries to enact the universal hepatitis B vaccination programme for newborn babies in 1992, and has made tremendous achievements in the control of hepatitis B virus (HBV) infection since then. China now has both low and high endemic regions regarding HBV prevalence coexisting. Although ChinaÕs drive to stop HBV spread has resulted in changes in HBV epidemic patterns, for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 18 publications
0
64
2
Order By: Relevance
“…In our study, the prevalence of anti-HBc (35.7%) and HBsAg (11.1%) among our controls was not lower than the prevalence rate of 30.08 and 9.75% in 1992 in China. 17 Here, we reported an association between chronic infection with HBV and the risk of pancreatic cancer. Furthermore, our results suggested that people who past exposed to HBV (anti-HBc-positive) with evidence of HBV immunity or recovery (anti-HBs-positive) might have a lower risk of pancreatic cancer than those with chronic carrier of HBV (HBsAgpositive/anti-HBc-positive).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In our study, the prevalence of anti-HBc (35.7%) and HBsAg (11.1%) among our controls was not lower than the prevalence rate of 30.08 and 9.75% in 1992 in China. 17 Here, we reported an association between chronic infection with HBV and the risk of pancreatic cancer. Furthermore, our results suggested that people who past exposed to HBV (anti-HBc-positive) with evidence of HBV immunity or recovery (anti-HBs-positive) might have a lower risk of pancreatic cancer than those with chronic carrier of HBV (HBsAgpositive/anti-HBc-positive).…”
Section: Discussionmentioning
confidence: 85%
“…China has now fallen into an intermediate endemic area where HBsAg prevalence rate in the general population is 2-7%. 17 However, infection with HBV is a systemic infectious process. Findings from previous study indicated that HBV DNA sequences were detected in the pancreas, kidney and skin, demonstrating HBV infection of these organs.…”
mentioning
confidence: 99%
“…HBV infection is endemic in some developing countries, including China, affecting nearly 15% of the population (Zhao et al, 2001;Sun et al, 2002;Lu et al, 2010). Meanwhile, Lung cancer is the most commonly diagnosed cancer and the leading cause of cancer death among men and women in China, contributing to 0.5 million deaths each year (Xie et al, 2012;She et al, 2013;Deng et al, 214;Liu et al, 2014).…”
Section: )mentioning
confidence: 99%
“…Due to high prevalence of hepatitis B virus (HBV) infection and cancer in some developing countries, especially China, concurrent infection with HBV is not uncommon in cancer patients (Sun et al, 2002;Lu et al,2010;Xie et al, 2012;She et al, 2013;Deng et al, 2014;Liu et al, 2014). Recently, the association of HBV infection and cancer has been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study has estimated that 93 million individuals of the Chinese population are infected with chronic HBV, which may eventually result in significant public health problems in the future (29). Patients with HBV infection that is accompanied by cirrhosis are in high risk of hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%